Activated phosphodiester as model compounds for RNA cleavage - Koski, Jasmin (My University, 2024)
Phosphodiester bond cleavage reaction has gained significant attention for potential biotechnological and pharmacological applications. Phosphodiester bonds are prevalent structures found in both DNA and RNA, while phosphate esters are also found in carbohydrates and their conjugates. Recent studies have focused on using RNA model compounds to develop artificial nucleases, aiming to replicate the catalytic efficiency of natural enzymes. Among these models, one 2-hydroxypropyl phosphate model compound, HPNP, has been widely used since it has offered a simplified approach despite its structural differences from natural occurring RNA. This study explores three RNA model compounds, HPNP and its analogues HPHP and HPCP, with the aid of kinetic methods to expose their individual features regarding phosphodiester cleavage reaction. The results provide comparable data to naturally occurring RNA transesterification reaction and help to assess the suitability of the compounds. Experimental methodologies reflect transition state theory, with results based on calculations acquired from a modified Eyring equation. Kinetic measurements were divided into two reaction phases for the model compounds, exploring their reactivity at different temperatures and pH levels. Samples were withdrawn from each reaction solution in suitable intervals and analyzed with RP-HPLC. The collected HPLC-data was further analyzed to comprehend reaction kinetics and the mechanism behind the transesterification reactions. Unlike some previous studies on similar small model compounds, which have shown isomerization affecting reactivity, HPNP and its analogues showed no such variation. HPNP demonstrated faster reaction rates due to its superior leaving group character compared to HPCP and HPHP. The pH-rate profiles exhibited minimal variations between compounds, resembling previously reported research data obtained with similar small molecular models. Calculated moderately negative βLG values suggested the nucleophilic attack being the rate limiting step of the reaction. The activation parameters indicated positive enthalpy (∆H≠) and negative entropy (∆S≠) of activation in variable levels for each model compound, with lowered activation energy barriers in acid catalyzed reactions. This study offers unique insight into the phosphodiester cleavage reaction of RNA model compounds, while deepening out understanding of 2-hydroxypropyl phosphates’ reactivity. The results support previous findings regarding the potential of 2-hydroxypropyl phosphates as artificial nucleases, despite their structural differences from natural RNA characteristics concerning nucleophiles and leaving groups. The findings of this study contribute to the ongoing development of RNA model compounds for biotechnological and pharmacological purposes. The results of this study on 2-hydroxypropyl phosphates of HPHP, HPCP and HPNP represent the first full kinetic analysis reported to date.
Keywords: Phosphodiester bond cleavage, RNA model compounds, Kinetic methods, Transesterification reaction, 2-hydroxypropyl phosphates